Glycemic control and pregnancy outcomes in women with type 2 diabetes from Poland. The impact of pregnancy planning and a comparison with type 1 diabetes subjects - Cyganek, Katarzyna; Hebda-Szydlo, Alicja; Skupien, Jan; Katra, Barbara; Janas, Izabela; Borodako, Alicja; Kaim, Irena; Klupa, Tomasz; Reron, Alfred; Malecki, Maciej T. (Endocrine, 2011)
The number of pregnancies complicated by type 2 diabetes mellitus (T2DM) is growing; however, their clinical characteristics remain incomplete. We aimed to assess clinical characteristics, glycemic control, and selected pregnancy outcomes in pregestational T2DM from Poland and to compare them with those of T1DM. We analyzed 415 consecutive singleton pregnancies; among them, there were 70 women with T2DM and 345 with T1DM. As compared to T1DM patients, women with T2DM were older (mean age 33.1 years vs. 27.8, respectively), heavier before pregnancy (mean BMI 30.8 kg/m² vs. 23.9), and had a shorter duration of diabetes (mean 3.3 years vs. 11.4); ( P < 0.0001 for all comparisons). The gestational age at the first visit was higher in T2DM (mean 11.4 weeks vs. 8.6; P = 0.0004). Nevertheless, they had better glycemic control in the first trimester (mean HbA1c 6.2% vs. 7.0; P = 0.003); in subsequent months, the differences in HbA1c were no longer significant. T2DM women gained less weight during pregnancy (mean 9.9 kgs vs. 14.1; P < 0.0001). The proportion of miscarriages (10.0 vs. 7.3%; P = 0.32), preterm deliveries (12.7 vs. 17.8%; P = 0.32), combined infant deaths, and congenital malformations were similar in both groups (9.5 vs. 8.8%; P = 0.4) as was the frequency of caesarean sections (58.7 vs. 64.1%; P = 0.30). Macrosomic babies were more than twice less frequent in T2DM and the difference reached borderline significance (7.9 vs. 17.5%, P = 0.07). Pregnancy planning in T2DM had a significant impact on HbA1c in the first trimester (5.7 vs. 6.4% in the planning vs. the not planning group, P = 0.02); the difference was not significant in the second and third trimester. T2DM women had better glycemic control in the first trimester than T1DM subjects and gained less weight during pregnancy. This could have been the reason for the slightly lower number of macrosomic babies but did not affect other outcomes. In T2DM, pregnancy planning had a beneficial glycemic effect in the first trimester.